Nutritional profiles according to socioeconomic levels and the menu offered in a community restaurant from Mexico - Miramontes-Escobar, Herenia Adilene; Prado-Guzmán, Gladys América; Toledo-Palomera, María de Jesús; Báez-García, Jesús Enrique; Sáyago-Ayerdi, Sonia Guadalupe (Universidad y Salud, 2020)
Introduction: Mexico is one of the main countries that face a nutritional problem caused by a deficit or excess of nutrients that causes malnutrition or overweight to the Mexican population. Objective: To identify the eating habits between three different social strata (ES) (low, medium and high) to compare it with the nutritional profile in a social canteen that offers breakfast and lunch in the City of Tepic, Nayarit. Materials and methods: These are surveys in the different social strata that correspond to a reminder of a day of breakfast and lunch with their snacks and drinks. Results: Protein consumption was found that exceeded the recommended daily intake, low consumption of dietary fiber (associated with low intake of fruits and vegetables) and high incidence in consumption of carbonated drinks. In addition, the highest total caloric intake was the high ES (attributed to its greater purchasing power), followed by the social canteen, however, neither ES nor the social canteen affected a balanced diet. Conclusions: The purchasing power of the different socioeconomic strata is not the main factor that limits a balanced diet, if not the lack of information and bad food of the Mexican population due to the loss of food culture.